PENGEMBANGAN BUKU SAKU TOILET TRAINING ANAK AUTIS USIA 5-10 TAHUN - Fadli Surahman; Nunik Aprilia; Eka Lenggang Dianasari (JURNAL JUDIKHU, 2021)
This research background is because autism children parents don’t understand how to teach toilet training to their child and toilet training guide book used by teacher not explain the details. Based. This research use R & D (research and development) model. The result of data analysis show that toilet training pocket book for autism child aage 5-10 years old in anakbriiant special education school get a score : 1) result of average materials expert validation score 92,86% ; 2) result of design expert score minimal score 12, maximal score 48, result score 37 (77,08%) ; 3) small-scale trial score for parents : 88,3 % and teachers : 87,5%, lagre-scale trials score for parents : 90% and teachers 89%. The conclusion is product of toilet training pocket book for autism children age 5-10 years old can developed in AnakBriliant School, and it deserve to used as a guide book for parents and teachers.